Evaluation and Improvement of Ventilation System Inside Low-Cost Automation Line to Reduce Particle Contamination - Lamai Puangburee; Wutthikrai Busayaporn; Mongkol Kaewbumrung; Jatuporn Thongsri (My University, 2020)
Low-Cost Automation (LCA) line, a group of machines to manufacture hard disk drive’s components located inside a clean room of factory, confronted with a problem of particle contamination caused by improper ventilation system. This article aims to evaluate airflow and proposes solutions to improve the ventilation system of LCA line based on Computational Fluid Dynamics (CFD). By using actual operating conditions collected at the factory and Fluent CFD software, the simulation showed that airflow patterns in such areas were substandard. For example, the large areas of vortex with the air velocities were lower than 0.2 m/s in critical areas: Fan Filter Units’ conveyor and Work Area. The low velocity of the airflow may cause the particle contamination and leads to the low-quality products. To reduce the particle contamination, we suggested novel solutions to the contamination problem. The CFD results revealed that our suggestions by increasing the momentum source (Sm) and/or redesign the LCA’s model by extending its height of cover where the increasing of Sm represented the increment of air velocity released from sources to the optimal values exhibited the decreasing of the vortex areas and also improved the air velocities in the critical areas to meet the factory’s standard.
Keywords: Factory (object-oriented programming); Contamination control; Particle (ecology); Aerosol Filtration and Electrostatic Precipitation